A microindentation two-fold creep model for characterizing short- and long-term creep behavior of a cement paste. (November 2020) - Chen, Zhao; Frech-Baronet, Jessy; Sorelli, Luca
Abstract: Owing to the micrometric size of the probed volume and the minute duration of a test, microindentation provides a unique tool to characterize the non-aging creep properties of a cement paste in hygral equilibrium. Microindentation techniques have been emerging as rapid technique to characterize the logarithmic creep rate of cement pastes. The objective of this study is to develop the analytical microindentation solutions of modern creep models, such as Microprestress-Solidification theory (MPS), Generalized Kelvin-Voigt model (GKV), and a recent microindentation two-fold creep model (M2C), which considers viscoelastic strain in series with a viscous flow strain of which viscosity is exponentially dependent on the viscous flow deformation, to provide a rapid calibration method. To minimize the effect of residual clinker, a cement paste with a water-to-cement ratio of 0.42 was cured for one year before testing. Subsequently, a microindentation grid of both creep and relaxation tests was carried out by employing a spherical tip at low penetration depth to reduce inelastic deformation. The microindentation analytical solutions of the aforementioned creep models were developed and its dual relaxation response was numerically developed. Microindentation creep and relaxation tests were employed to calibrate and validate the creep parameters, respectively. While microindentation allowed identifying the parameters of the considered creep models in a satisfactory manner, the implemented M2C creep model permitted to gain insight into the two-fold basic creep mechanism from a microindentation perspective. Highlights: Developed microindentation analytical creep models of existing concrete creep models. Rapid model parameters calibration by microindentation creep tests on a cement paste. Distinguished viscoelastic and logarithmic basic creep mechanisms. Found creep mechanisms' interaction during relaxation due to stress redistribution.